Fonologi: Perencanaan, pelaksanaan, dan evaluasi pembelajaran - Abidah, Faizah Nurul (Maliki Interdisciplinary Journal, 2023)
Phonology has language elements that discuss sound elements or the release of spoken language properly. This language element is very important for students to master. Knowing the effectiveness of the use of learning in Indonesian phonology. Phonology is related to the sounds of language produced by human speech organs. Phonology is a branch of linguistics that studies the sounds of language in general. Every day, we will not be separated from the sound of language. Because language is a means of communication between humans. Phonology includes elements of language as a means of human speech and is very important to be mastered by students to find out the effectiveness of using learning in Indonesian phonology.